Silicon-on-insulator free-carrier injection modulators for the mid-infrared - Nedeljkovic, Milos (2020)
Experimental demonstrations of silicon-on-insulator waveguide-based free-carrier effect modulators operating at 3.8 μm are presented. PIN diodes are used to inject carriers into the waveguides, and are configured to (a) use free-carrier electroabsorption to create a variable optical attenuator with 34 dB modulation depth and (b) use free-carrier electrorefraction with the PIN diodes acting as phase shifters in a Mach-Zehnder interferometer, achieving a VπLπ of 0.052  V·mm and a DC modulation depth of 22 dB. Modulation is demonstrated at data rates up to 125 Mbit/s.